Sources of Paul’s Teaching (Thoughts) - Warseto Freddy Sihombing; Pelealu Samuel G (LPPM IAKN Tarutung, 2022)
Where is the source of Paul's teachings or thoughts? This becomes an important and serious question when we open the New Testament. Some of the things that are of concern are that there are many letters written by Paul and in his writings, there are many doctrines and theological terms that are very inherent in the church. If we look at the background of Paul's life, we will feel astonished. The question that follows the above is why his writings really dominate the New Testament while he is not an apostle directly chosen by Jesus as with Simon Peter, Andrew, James, etc.? What is the main source for all of Paul's writings so that they dominate the New Testament? Where are the main sources of his teaching?